Fixed Investment and Capital Flows : A Real Options Approach - Chan-Lau, Jorge (IMF Working Papers; Working Paper ;, 1998)
This paper draws a link between international capital flows and the real options approach to investment by extending a model of real estate investment. It explains gradual investment, investment booms, and investment during recessions and emphasizes sunk costs, uncertainty, and the value of waiting. The optimal waiting time increases as foreign borrowing becomes more expensive because higher returns are required to cover the sunk costs of investing. The lower the initial level of profitability, the more likely investment will be sequential; conversely, a relatively high initial rate of return will be associated with simultaneous investment.